2019
DOI: 10.1037/pag0000389
|View full text |Cite
|
Sign up to set email alerts
|

Cohort differences in adult-life trajectories of internal and external control beliefs: A tale of more and better maintained internal control and fewer external constraints.

Abstract: html), and the Berlin Aging Study II (BASE-II; https://www.base2.mpg.de/ en). First, the BASE was initiated by the late Paul B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 91 publications
5
41
0
Order By: Relevance
“…Given that sexuality is considerably shaped by historical and social circumstances (Pettit & Hegarty, 2014), it stands to reason that attitudes toward sexuality differ across historical time and contribute to the occurrence of cohort differences in sexual behaviors and experiences (Mercer et al, 2013;Twenge et al, 2017). Additionally, historical changes in several life domains in late midlife that are closely intertwined with sexual functioning such as lower levels of loneliness (Suanet & van Tilburg, 2019) and higher levels of internal control among later-born cohorts (Gerstorf et al, 2019)…”
Section: Introductionmentioning
confidence: 99%
“…Given that sexuality is considerably shaped by historical and social circumstances (Pettit & Hegarty, 2014), it stands to reason that attitudes toward sexuality differ across historical time and contribute to the occurrence of cohort differences in sexual behaviors and experiences (Mercer et al, 2013;Twenge et al, 2017). Additionally, historical changes in several life domains in late midlife that are closely intertwined with sexual functioning such as lower levels of loneliness (Suanet & van Tilburg, 2019) and higher levels of internal control among later-born cohorts (Gerstorf et al, 2019)…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that old age has changed with historical time and "gotten younger" in several important aspects (Gerstorf et al, 2015), including perceptions of control. Gerstorf and colleagues (Gerstorf et al, 2019) suggest several reasons as to why the historical context should affect levels and trajectories of control beliefs. First, early life experiences of earlier born cohorts were characterized by dramatic events that left little control to individuals.…”
Section: Historical Differences In Perceived Controlmentioning
confidence: 99%
“…In the current study, historical differences simply refer to differences between individuals at different historical time points (cf. Drewelies et al, 2019;. More specifically, we compare individuals retiring at different historical time points.…”
Section: Introductionmentioning
confidence: 99%
“…Although different terms are used, all refer to individuals' belief and expectation that their actions can affect their world (Mirowsky & Ross, 1998). Sense of control is a vital psychological resource, repeatedly found to predict positive outcomes such as psychological wellbeing, physical health, and mortality (for reviews, see Gerstorf et al, 2019, Slagsvold & Sørensen, 2013. These positive outcomes are primarily related to the beliefs about being able to control, regardless of whether these beliefs are correct or not (Skinner 1996).…”
Section: The Boomers As Agentic and Expecting Influence And Controlmentioning
confidence: 99%